PENYAJIAN LAPORAN KEUANGAN PEMERINTAH DESA STUDI PADA PEMERINTAH DESA BAWAK KECAMATAN CAWAS KABUPATEN KLATEN - Diah Aryanti Sapto Warsi; Handayani Handayani (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2019)
This research is meant to find out the presentation of financial statement of Bawak village,Cawas Sub-district, Klaten district in 2016 has been presented in accordance with the PERMENDAGRI No. 113 of 2014 about the Financial Management of the village.The research method has been carried out by using descriptive research method and qualitative approach. The data has been conducted by using primary and secondary data as the sources. The primary data has been obtained from the interview which is relevant to the presentation of financial statement. It has been found from the result of this research that the presentation of financial statement of Bawak village is based on the PERMENDAGRI No. 113 of 2014 which shows the accountable and transparent implementation which can be reviewed from the responsibility statement of village government budget (APBDesa).